Types of Coronary Atherosclerosis Flow in Patients with Coronary Interventions in Anamnesis - Knyshov, G. V.; Levchyshyna, O. V.; Aksonov, Ie. V.; Nastenko, Ie. A. (Ukrainian Journal of Cardiovascular Surgery, 2016)
Coronary atherosclerosis continues to be one of the most pressing health problems in the world, despite the continuous expansion of drug therapy, the increasing number of coronary stenting and bypass surgery. Perhaps further depth study of this pathological process will help identify the ‘target points “ that will stop the progression of the disease.